Environmental education in high school in young and adult education in Ilha Solteira city (SP - Brazil) - Alkimin, Gilberto Dias de [UNESP]; Dornfeld, Carolina Buso [UNESP] (Federal Univ Rio Grande, Inst Education, 2016)
The National Policy Environmental Education (PNEA) presents in his text that Environmental Education (EE) should be present at all levels and types of education. This work aimed to study the inserction of EE in High Shcool in Youth and Adults Education in the Ilha Solteira city - Sao Paulo/Brazil. The instrument used for data collection was a questionnaire for students and analysis of results was made of qualitative and quantitative way, using textual analysis. The results indicate that students have deficiency of knowledge of environmental issues and their participation in projects is as scarce as the supply of projects by the school for this type of education.
Keywords: High School; Public Policies; Environmental Perception